PENGARUH KARAKTERISTIK PEKERJAAN DAN KONFLIK PERAN (ROLE CONFLICT) TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA - Yusi Irasanti, 12.4202.0050; Setyowati, Widhy (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to determine the effect of job characteristic and role conflict on employee’s performance, mediating by job satisfaction. The respondens are all Unit’s treasurers of Health Office, in Pati Distric. The sample of this research is all 106 treasures (sensus). Statistical technique used was to test the validity of componen matrix, alpha cronbach reliability test, regression analysis, adjusted R square, f test , t tes n mediating test. Survey result revealed that job characteristic had a significant positive efect on job satisfaction, while role conflict had unsignificant negative effect on job satisfaction. Job Characteristic significanly negative influent on employee’s performance. Role conflict  effect on emlpoyee’s performance negative and not significant.Job satisfaction gave significantly possitive effect on employee’s performance. Job characteristis undirect effect on employee’s performanc is better then it’s direct effect. It mean that job satisfaction does mediating job characteristic on employee’s performance. Unfortunally, role conflict effect is not significant , so there’s no mediating effect. Keyword : Job Characteristic, Role Conflict, Job Satisfaction and Employee’s  Performance